PARADIGMA PEMBELAJARAN BAHASA ARAB DI ERA SOCIETY 5.0 - Syagif, Ahmad (FiTUA: Jurnal Studi Islam, 2022)
The existence and need to learn Arabic remains a strategic issue in the midst of the dynamics of the changing times, especially in the current era of Society 5.0. This era has a basic concept in the form of transforming a conventional way of life to a digital one. This has an impact on all aspects of human life including Arabic education and learning. Among the challenges that await the world of education in the era of Society 5.0 is how to bring science and technology together without sacrificing students. That's why, through this literature review, the author wants to conduct a theoretical and factual study of the paradigm of learning Arabic in the era of society 5.0. So it was found that there was a significant shift in the paradigm of learning Arabic in various aspects starting from the orientation of learning, demands for teacher qualifications and learning models, demands for student competence and learning character, to the need for facilities and supporting facilities. Regardless of the pluses and minuses, all parties and stakeholders involved in Arabic learning activities must be willing to improve in order to be able to maintain their existence in this digital era.